1999
DOI: 10.2307/2641337
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Effects of Biodiversity: A Classification of Hypotheses and Exploration of Empirical Results

Abstract: The increasing evidence for effects of biodiversity on ecosystem properties and processes indicates that effects may vary strongly over the range of studied systems. In order to explore patterns and draw some preliminary conclusions on biodiversity effects in different ecological contexts, we have compiled empirical data from original studies and reviews on effects of biodiversity in natural, agricultural, and forestry systems. We classified hypotheses according to observed ecosystem variables and trophic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
153
2
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(168 citation statements)
references
References 54 publications
6
153
2
7
Order By: Relevance
“…However, although highly productive species do indeed make consistent and sizeable contributions to plant biodiversity effects, these are equaled or exceeded in frequency and magnitude by multispecies contributions to biomass. Our finding that the net effects of plant diversity on biomass are generally positive corroborates what appears to hold true for many types of organisms in ecosystems around the globe (10,11,(13)(14)(15)36). However, our finding that diverse polycultures tend to achieve less biomass than their most productive species contrasts with a common prediction in diversity-function research.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, although highly productive species do indeed make consistent and sizeable contributions to plant biodiversity effects, these are equaled or exceeded in frequency and magnitude by multispecies contributions to biomass. Our finding that the net effects of plant diversity on biomass are generally positive corroborates what appears to hold true for many types of organisms in ecosystems around the globe (10,11,(13)(14)(15)36). However, our finding that diverse polycultures tend to achieve less biomass than their most productive species contrasts with a common prediction in diversity-function research.…”
Section: Discussioncontrasting
confidence: 55%
“…Seminal experiments in this field focused on characterizing how plant species richness affects primary production (e.g., refs. 7 and 8), and generally showed that reducing the number of herbaceous plant species leads to less efficient use of soil nutrients and lower production of biomass (9)(10)(11). These experiments not only articulated the hypothesis that species loss can affect important ecological processes, they spawned a decade of experiments in which researchers manipulated the diversity of a wide variety of organisms to see how this impacts the functioning of many different ecosystems (12).…”
mentioning
confidence: 99%
“…Plant species richness was highest at intermediate vehicular disturbance levels in one study (Leis and others 2005), and tracked vehicles caused greater vegetation change in British chalk grassland than wheeled vehicles (Hirst and others 2003). It has also been shown that plant diversity levels can affect resistance and resilience to disturbance (Schläpfer and Schmid 1999). Lastly, a qualitative review by Yorks and others (1997) suggested that graminoids show the highest resistance and resilience to vehicle and trampling disturbance while broad-leaved forbs tend to suffer immediate losses from disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining the provision of these goods and services in the face of natural and anthropogenic disturbances is critical to achieving both conservation and economic goals. Motivated by accelerating rates of worldwide decline in biodiversity (2), considerable research has focused on the conse quences of local species loss for goods and services provided by ecosystems (2)(3)(4)(5)(6)(7)(8). Much of this work focuses on the effects of declining species richness on short-term processes such as production, community respiration, and nutrient cycling (2).…”
mentioning
confidence: 99%
“…9), it does appear that, in some systems, reductions in local species diversity contribute to a decline in ecosystem properties such as productivity and resistance to disturbance (see review in ref. 2).…”
mentioning
confidence: 99%